Pozycja aktora w obliczu rozwoju platform streamingowych - Cebera, Marta (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2024)
The article analyzes an actor’s position in the face of the development of streaming services. The author uses the comparative method to present analogies and differences in how the old study system and the new streaming system function, with particular emphasis on the hierarchy in the industry, attitude to actors, work culture and wage inequalities. She draws attention to the advantages of the flourishing VOD platforms and contrasts this with the losses suffered by actors. The article recalls earlier disputes between artists and studios, which are compared with such issues as reasons of SAG-AFTRA strike in 2023, residuals for creators on the digital market, and artificial intelligence in filming. History has come the full circle: platforms have grown into a hegemon in this business and replicate old strategies.